Analysis of biosurfactants from industrially viable Pseudomonas strain isolated from crude oil suggests how rhamnolipids congeners affect emulsification property and antimicrobial activity - Das, Palashpriya; Yang, Xin-Ping; Ma, Luyan Z. (Frontiers in Microbiology, 2014)
Rhamnolipid biosurfactants produced mainly by Pseudomonas sp. had been reported to possess a wide range of potential industrial application. These biosurfactants are produced as monorhamnolipid (MRL) and di-rhamnolipid (DRL) congeners. The present study deals with rhamnolipid biosurfactants produced by three bacterial isolates from crude oil. Biosurfactants produced by one of the strains (named as IMP67) was found to be very efficacious based on its critical micelle concentration (CMC) value and hydrocarbon emulsification property. Strikingly, antimicrobial and anti-biofilm potential of this biosurfactant were higher than biosurfactants produced by other two strains. Thin layer chromatography (TLC) analysis and rhamnose quantification showed that the rhamnolipids of IMP67 had more MRL congeners than biosurfactants of the other two strains. Emulsification and antimicrobial actions were affected by manual change of MRL and DRL congener proportions. Increase of MRL proportion enhanced emulsification index and antimicrobial property to Gram negative bacteria. This result indicated that the ratio of MRL and DRL affect the emulsification potentials of rhamnolipids, and suggested that high emulsification potentials might enhance rhamnolipids to penetrate the cell wall of Gram negative bacteria. In consistent, rhamnolipids of IMP67 reduced the MIC of some antibiotics against bacteria, suggesting the potential of biosurfactant as antibiotics synergist.